Associations between the chemokine biomarker CCL2 and knee osteoarthritis outcomes: the Johnston County Osteoarthritis Project. Issue 9 (September 2018) - Longobardi, L.; Jordan, J.M.; Shi, X.A.; Renner, J.B.; Schwartz, T.A.; Nelson, A.E.; Barrow, D.A.; Kraus, V.B.; Spagnoli, A.
Summary: Objective: Our study analyzes the association between chemokine-ligand-2 (CCL2) serum concentrations at baseline and knee radiographic osteoarthritis (OA) (knee-rOA), knee-rOA progression, individual radiographic features and knee symptomatic OA at 5-year follow-up. Design: OA outcomes were analyzed in a community-based cohort including a baseline enrollment and a 5-year follow-up. Baseline CCL2 serum concentrations were assessed by multiplex assay and associated with presence or progression of individual radiographic features at 5-year follow-up. Separate multiple logistic regression models were used to examine adjusted associations between baseline CCL2 and each of the knee OA variables at follow-up. CCL2 at baseline was modeled as an explanatory variable, whereas each of the knee OA variables at follow-up served as the response variables. Models were adjusted for age, BMI, race, and sex. Trend tests were conducted to assess any linear effect on outcomes across CCL2 tertiles. Results: Participants ( n = 168) had a median age of 57-years and median BMI of 29 kg/m2. About 63% of all participants were women, and 58% Caucasian (42% African American). In adjusted logistic models, continuous log-CCL2 was significantly associated with knee-rOA. For each unit increase in log CCL2, the odds of having knee-rOA at follow-up was increased by 72%. CCL2 tertiles showed significant linear associations with presence and progression of knee-rOA and medial joint space narrowing (JSN), but not with presence or progression of osteophytes, bone sclerosis, knee symptoms, or symptomatic knee-rOA. Conclusions: Serum CCL2 may help to elucidate some mechanisms of joint destruction and identify individuals with higher odds of structural knee changes.